Systematic Review: Faktor yang Berperan terhadap Efektivitas Penggunaan APD dalam Mencegah Transmisi Covid-19 pada Tenaga Kesehatan - Neng Salma Arina Azmi; Maya Tejasari; Listya Hanum (UNISBA Press, 2023)
Abstract. The Coronavirus Disease (COVID-19) pandemic started first in Wuhan, China and listed as a pandemic by the World Health Organization (WHO). Health workers(HCW) treat COVID-19 patients directly, so the risk of infection with SARS-CoV-2 is higher than the general population. During the COVID-19 pandemic, personal protective equipment (PPE) has become a necessity. In particular, HCW need PPE to protect against the spread of infection. 1 The use of PPE can reduce the risk of infection associated with treating COVID-19 patients, to prevent the transmission of the SARS-Cov-2 virus must use PPE. PPE includes masks, gloves, eye protection, and gowns needed to protect individuals from exposure to the virus SARS-CoV-2. So this study aims to determine the Effectiveness of Using PPE in Prevention of COVID-19 Transmission in HCW. The type of research used is a systematic review using 3 databases ScienceDirect, SpringerLink, and Pubmed. then selected articles for 2020–2022 with an Observational research design and a special design. on data searching, 17,337 articles were found, and 818 articles were obtained. Then a PICOS analysis was carried out and 15 articles were obtained that would be critically reviewed and the results were 7 articles. From 7 articles, a relationship was obtained between the use of PPE in preventing the transmission of COVID-19 and influencing factors such as availability, quantity, training, compliance and type of use of PPE. Using respirator masks and N95 surgical masks is superior to disposable masks or cloth masks in reducing the spread of the virus because they have the highest filtration efficiency and reduce aerosol penetration >96.67% at a distance of 0–1.5 m. Abstrak. Pandemi Coronavirus disease (COVID-19) dimulai pertama kali di Wuhan, Cina dan terdaftar sebagai pandemi oleh World Health Organization (WHO). Tenaga kesehatan menangani pasien COVID-19 secara langsung sehingga berisiko lebih tinggi terinfeksi SARS-CoV-2 daripada populasi umum. Selama masa pandemic COVID-19, alat pelindung diri (APD) telah menjadi kebutuhan. Secara khusus, tenaga kesehatan membutuhkan APD untuk perlindungan terhadap penyebaran infeksi. Penggunaan APD dapat mengurangi risiko infeksi terkait dengan perawatan pasien COVID-19, untuk mencegah transmisi virus SARS-Cov-2 harus menggunakan APD. APD meliputi mask, hand gloves, eye protector, dan gown diperlukan untuk melindungi dari paparan virus SARS-CoV-2. Jenis penelitian yang digunakan adalah systematic review menggunakan 3 database ScienceDirect, SpringerLink, dan Pubmed. kemudian dipilih artikel tahun 2020–2022 dengan desain penelitian Observational dan design khusus. Pada pencarian data didapatkan 17,337 artikel dan pada skrining didapatkan 818 artikel. Kemudian dilakukan analisis PICOS dan didapatkan 15 artikel yang akan ditelaah kritis dan hasilnya 7 artikel. Dari 7 artikel diperoleh hubungan antara penggunaan APD dalam mencegah transmisi COVID-19 dengan faktor yang mempengaruhi seperti ketersediaan, kuantitas, peltihan, kepatuhan dan jenis penggunaan APD. Menggunakan masker respirator dan masker bedah N95 lebih unggul dibandingkan masker sekali pakai atau masker kain dalam mengurangi penyebaran virus karena memiliki efisiensi filtrasi tertinggi dan mengurangi penetrasi aerosol >96,67% pada jarak 0–1,5 m.